Implementation of Advanced SQL Using Java Server Pages as Frontend - Nur Atikah Arbain; Abdul Razak Hussain; Norhayati Harum; Mohd Sanusi Azmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
In web-based applications, communication between web (frontend) and database (backend) is crucial as it is not only used to store and retrieve data but also to perform other processes either at the frontend or backend. However, the process that is performed at frontend could lead to data leak due to weak security. Therefore, this paper presents the idea by storing all process including prepared statements of Create, Retrieve, Update and Delete (CRUD) and calculations into database using PL/SQL programming language (Oracle) where web based of Java Server Pages (JSP) is used as a frontend. The framework of Model View Controller (MVC) is applied as the guideline to handle the development of web based. Besides events advanced SQL such as stored procedures, functions and trigger event are implemented where they are used to commit the operation of CRUD. As the output, all operation of CRUD, calculation, error handling (exception handlers) is committed and process at backend while frontend is used only to display data and send input from user. As conclusion, the transaction data between web and database can be secured as well as all processes are performed in the database.